2009
DOI: 10.1111/j.1742-4658.2009.07443.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of the metal ion‐dependent l‐alanoyl‐d‐glutamate peptidase encoded by bacteriophage T5

Abstract: Although bacteriophage T5 is known to have lytic proteins for cell wall hydrolysis and phage progeny escape, their activities are still unknown. This is the first report on the cloning, expression and biochemical characterization of a bacteriophage T5 lytic hydrolase. The endolysin‐encoding lys gene of virulent coliphage T5 was cloned in Escherichia coli cells, and an electrophoretically homogeneous product of this gene was obtained with a high yield (78% of total activity). The protein purified was shown to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 57 publications
(61 reference statements)
3
52
0
Order By: Relevance
“…Considering that Zn 2+ obviously assumes a crucial role in catalytic function of these enzymes, it was surprising to find that Ca 2+ and Mn 2+ were more effective in restoring lytic activity after . Similar observations regarding the effects of divalent metals on activity of cell wall hydrolases were reported earlier (Vasala et al 1995;Shida et al 2001;Pritchard et al 2004;Donovan et al 2006;Sugahara et al 2007;Mikoulinskaia et al 2009;Garcia et al 2010). For aminopeptidase A, a zinc metalloendopeptidase that can be reactivated by Ca 2+ or Mn 2+ after exposure to chelating agents (Danielsen et al 1980), it was recently shown that the Ca 2+ ion increases substrate affinity by binding to two aspartate residues of the enzyme and interacting with an acidic side chain of the substrate (Claperon et al 2008).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Considering that Zn 2+ obviously assumes a crucial role in catalytic function of these enzymes, it was surprising to find that Ca 2+ and Mn 2+ were more effective in restoring lytic activity after . Similar observations regarding the effects of divalent metals on activity of cell wall hydrolases were reported earlier (Vasala et al 1995;Shida et al 2001;Pritchard et al 2004;Donovan et al 2006;Sugahara et al 2007;Mikoulinskaia et al 2009;Garcia et al 2010). For aminopeptidase A, a zinc metalloendopeptidase that can be reactivated by Ca 2+ or Mn 2+ after exposure to chelating agents (Danielsen et al 1980), it was recently shown that the Ca 2+ ion increases substrate affinity by binding to two aspartate residues of the enzyme and interacting with an acidic side chain of the substrate (Claperon et al 2008).…”
Section: Discussionsupporting
confidence: 64%
“…In fact, most other phage and bacterial lysins studied require neutral or slightly acidic conditions, with activity rapidly decreasing above pH 7.5 or 8 (Vasala et al 1995;Morita et al 2001;Loeffler et al 2003;Pritchard et al 2004;Yoong et al 2004;Cheng and Fischetti 2006;Donovan et al 2006;Fukushima et al 2007;Sugahara et al 2007). However, another L-alanoyl-D-glutamate peptidase from E. coli phage T5 revealed a pH profile similar to the enzymes reported here, with highest activity at pH 8.5 (Mikoulinskaia et al 2009). It is interesting to note that these properties correspond well to the optimum range for Listeria, which also grows best at a pH of around 8.0 (Vanderzant and Splittstoesser 1992).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In opposition to what is described by Pfam, the Listeria phage endolysins Ply118 and Ply500 and the enterobacteriophage T5 endolysin classified as VANY carboxypeptidases act as L-alanyl-D-glutamate endopeptidases (56,57). PET-M15-4 is a domain also described as D-alanyl-D-alanine carboxypeptidase; however, it has been predicted to display L-Ala-D-Glu activity (54).…”
Section: Resultsmentioning
confidence: 62%
“…Conserved domain analysis revealed the presence of a VanY Pfam (SMART) and a peptidase M15_4 (CDD), both of which are described as a D-alanyl-D-alanine carboxypeptidase. Contrary to what has been described, it has been experimentally reported that Listeria phage endolysins Ply118 and Ply500 and the endolysin from bacteriophage T5, although classified as putative D-alanyl-D-alanine carboxypeptidases, actually display L-alanyl-D-glutamate activity (Loessner et al, 1995;Mikoulinskaia et al, 2009;Payne & Hatfull, 2012 Cerebrospinal fluid…”
Section: Host-cell Lysismentioning
confidence: 71%